Sex and the Empire That Is No More: Gender and the Politics of Metaphor in Oyo Yoruba Religion - Matory, J. Lorand (Berghahn Books, 2005)
Shows how the rivalry among Oyo Yoruba between the cults of the possessing god Shango and the nonpossessing god Ogun is related to contrasting values concerning the conduct of women in the political process from early to modern times. The conclusion includes probative remarks on the problem of intercultural translation.
paid
Keywords: Religion / Sexuality & Gender Studies; Social Science / Anthropology / Cultural & Social; Social Science / Gender Studies